Peran Lembaga Amil Zakat dan Sedekah dalam Pengentasan Kemiskinan di Indonesia - Nilawati; Ikhwan; Zulfan (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2024)
This article aims to analyze the potential contribution of zakat in Indonesia with several key focuses. First, the research will explore the impact of using zakat and charitable funds on the economic growth of Indonesian society. Second, the study will examine the influence of inflation rates on economic growth. Third, this research will investigate the methods used by zakat management institutions in Indonesia to distribute ZIS (zakat, infaq, and sedekah) funds and their impact on Indonesia's economic growth. The data for this study is obtained through articles, books, and documents. Meanwhile, document analysis is conducted to acquire data related to the instruments and media used by institutions to distribute zakat based on Sharia principles. The study finds that the distribution of zakat, infaq, and sedekah (ZIS) to the eight groups of beneficiaries, as prescribed in Islamic law, includes the poor, amil, converts, those in bondage, debtors, those striving in the path of Allah, and wayfarers. These groups are emphasized in Islamic teachings. Regional BAZNAS (National Amil Zakat Agency) is responsible for managing and distributing infaq and other religious social funds while adhering to Islamic legal principles and fulfilling the objectives expected by donors.